Analysis of the Role of the Tourism Industry on Morowali Regency's Original Revenue - Andi Herman Jaya; Frank Reyhard Baho; Aris Muhammad (Enrichment : Journal of Management, 2021)
Regional autonomy is closely related to the finances of a region, which is related to its income or Regional Original Income (PAD). Regional Original Revenue will bring its own implications for an area with limited natural resource potential and it will be a challenge in itself in an effort to maximize the potential possessed by the region. This study aims to analyze the ancer y contribution of tourism to local revenue, the effectiveness of tourism revenues, and the efficiency of tourism revenues. The type of data used in this study, namely the type of quantitative data in the form of periodic data. This study shows that the contribution of tourism revenue to Morowali Regency's Original Revenue is very small. Revenue from the tourism sector from 2014 to 2018 shows that the income of the tourism sector in Morowali Regency is inefficient and ineffective due to lack of income. The purpose of this research is to make a pilot in the tourism sector, so that planning and coordination of the contribution of the tourism sector in an effort to increase income continues.